Post activation potentation response of male vs. female collegiate badminton athletes - Manuel, Vincent Rafael G.; Valleser, Christian Wisdom M. (Quezon City College of Human Kinetics, University of the Philippines Diliman, 2019)
The aim of this study is to test if sex is a factor in post-activation potentiation response (PAP). To test for PAP response, twenty male (n=10) and female (n=10) collegiate badminton athletes underwent two protocols: weight training protocol(1 set, 5 repetitions of 5-RM trap bar deadlift) and control (no intervention) protocol. To test for leg power, the countermovement jump height will be measured using an inexpensive, portable approach named My Jump 2 App which uses the leg length subtracted by the height of the knees and ankles prior to take-off was used. A paired t-test will be used to compare the control versus the PAP protocol in each group while the difference between the post and pre-jumps will be tested using an independent t-test. Significant differences were then analyzed using Cohen's d. The level of significance will be set at the p<0.05 level. The paired T-tests have shown that there is a significant increase for the males in the control (p=0.007) and PAP protocol (p=0.001) while there were insignificant increases in both the control (p=0.061) and PAP protocol (p=0.172) for the females. The independent t-test showed that the response of PAP was significantly better for the males (p=0.019). In conclusion, a warm-up regime involving trap bar deadlifts with the same protocol may be used for short-term improvements for males but not for females. Therefore, it can be suggested that PAP response is more favorable for males as compared to females.
Vita.
Thesis (Bachelor in Sports Science)--University of the Philippines Diliman
Keywords: Badminton players; Badminton (Game) -- Training; Exercise -- Physiological aspects